A parvo-like virus in the giant freshwater prawn, Macrobrachium rosenbergii - Anderson, I.G.; Law, A.T.; Shariff, M.; Nash, G. (Elsevier, 1990)
During histological examination of postlarval Macrobrachium rosenbergii survivors of toxicity experiments, amorphous, basophilic intranuclear inclusions were apparent in hepatopancreatic tubule epithelial cells (Fig. 1). The postlarvae had been fixed in Davidson’s solution, stored in 50% ethanol, and processed routinely for histology as 5-pm sections stained with hematoxylin and eosin (H&E).